Gauging sediment thickness in a seismically prone city in the context of the recent 6.4 M Assam earthquake - Rajib Biswas; Nilutpal Bora (Results in Earth Sciences, 2025)
This work reports estimation of sediment thickness in a seismically prone city, namely Tezpur of Northeast, India via ambient noise measurements. Accordingly, a three-component broadband sensor was used to accrue ambient noise at seventy various locations of Tezpur. Estimation of resonance frequencies has been done from horizontal to vertical spectral ratios. Via as estimated resonance frequencies and available borehole feed, an empirical power law has been formulated which allows for boarder mapping of sediment thickness. The results indicate a predominance of lateral heterogeneity in the area under study. Apart from that, estimates of VS hint at diverse soil types existing in this region. All these inputs can be of help for geotechnical engineers as well as policy makers to foster earthquake resilience in the context of the recent 2021 6.4 MW earthquake whose epicenter was very nearby to the study area.